FAMILY SUPPORT AND MEDICATION ADHERENCE AMONG PATIENTS WITH SCHIZOPHRENIA IN PRIMARY HEALTHCARE - Nurkhalisah; Rusni Masnina; Ni Wayan Wiwin Asthiningsih (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Schizophrenia is a chronic mental disorder requiring long-term pharmacological treatment. Medication non-adherence remains a major challenge and contributes to relapse and rehospitalization. In primary healthcare settings, family support is considered a key psychosocial factor influencing medication adherence. Objectives: This study aimed to examine the association between family support and medication adherence among outpatients with schizophrenia in a primary healthcare setting. Methods: An analytical cross-sectional study was conducted at Puskesmas Loa Bakung Samarinda, Indonesia. A total of 40 schizophrenia outpatients were recruited using total sampling. Family support was measured using the Duke-UNC Functional Social Support Questionnaire, while medication adherence was assessed with the Morisky Medication Adherence Scale-8 (MMAS-8). Data were analyzed using univariate analysis and Chi-square or Fisher’s exact test, with odds ratio (OR) estimation at a significance level of p < 0.05. Results: Of the respondents, 52.5% reported sufficient to high family support, while 47.5% reported low support. Medication adherence was categorized as low in 57.5% of patients, moderate in 17.5%, and high in 25.0%. A significant association was found between family support and medication adherence (p = 0.022). Patients with low family support had a sixfold higher risk of non-adherence compared to those with sufficient or high family support (OR = 6.094). Conclusion: Family support is significantly associated with medication adherence among patients with schizophrenia in primary healthcare. Strengthening family involvement in community-based mental health services is essential to improve adherence and reduce the risk of relapse.